Numerical simulation of the beam-plasma turbulence spectrum evolution for weak beams - Anisimov, I.O.; Siversky, T.V. (Вопросы атомной науки и техники, 2003)
The results of the numerical simulation of weak non-relativistic monochromatic beam interaction with plasma are introduced. The modified PDP1 package for one-dimensional plasma systems simulation was used. Evolution of the phase portrait and electric field distribution during beam-plasma turbulence was investigated. Plasma oscillations spectra were obtained. Their temporal and spatial evolution was studied.